1998
DOI: 10.1002/j.1556-6978.1998.tb00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Counselor Education: Supervision, Teaching, and Clinical Training Revisited

Abstract: The goal of this project is to systematically reflect on the foundations of counselor education and, through the thoughtful analysis reflected in these contributions, to stimulate a broad discussion of its assumptive foundations. It is hoped that this will ultimately serve as the basis for a reconstructed model of counselor education.Since its foundation in 196 1 , the Counselor Education and Supervision journal has documented the growth of counselor education as a theoretical and professional endeavor. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…evaluated the developmental effects of counselor training programs on both conceptual and moral reasoning levels and found that clinical work was influential in promoting students' cognitive complexity. Sexton (1998) stated that the literature lacks a description of the art and science of counselor education and that the Council for the Accreditation of Counseling and Related Educational Programs (CACREP) sets forth the information that needs to be taught within counselor education programs but does not provide information on the most effective methods of presenting the material. Moreover, Nelson and Neufeldt (1998) reviewed the counseling pedagogy literature and found that most research focused on teaching specific concepts such as client conceptualization, theoretical acquisition, and specific counseling problems.…”
Section: Editorialmentioning
confidence: 99%
“…evaluated the developmental effects of counselor training programs on both conceptual and moral reasoning levels and found that clinical work was influential in promoting students' cognitive complexity. Sexton (1998) stated that the literature lacks a description of the art and science of counselor education and that the Council for the Accreditation of Counseling and Related Educational Programs (CACREP) sets forth the information that needs to be taught within counselor education programs but does not provide information on the most effective methods of presenting the material. Moreover, Nelson and Neufeldt (1998) reviewed the counseling pedagogy literature and found that most research focused on teaching specific concepts such as client conceptualization, theoretical acquisition, and specific counseling problems.…”
Section: Editorialmentioning
confidence: 99%
“…Of the available literature, the primary focus is on skill development rather than overall class design (Granello, 2000a;Nelson & Neufeldt, 1998;Sexton, 1998a;1998b). An examination of the rehabilitation counseling literature suggests limited attention as well.…”
mentioning
confidence: 99%
“…Adult students expect the material they are learning to have more relevance to them than is expected by younger students (an aspect Carver, 1996, regards as authenticity in education) and for the material to have more immediate and apparent application. Furthermore, faculty and administrators are being held more accountable for services provided due to the increased scrutiny of funding sources and accreditation boards (Lewis &Williams, 1994;Sexton, 1998b). Implementing the four processes of experiential education, therefore, can address the relevancy needs of adult learners and the accountability needs of faculty and academic programs today.…”
mentioning
confidence: 99%